SELF-EFFICACY, PSYCHOLOGICAL STRESS, FAMILY SUPPORT, AND EATING BEHAVIOR ON TYPE 2 DIABETES MELLITUS - Kusuma Wijaya ridi Putra; Chanandchidadussadee Toonsiri; Suwanna Junprasert (Belitung Nursing Journal, 2016)
Background: Diabetes mellitus (DM) is one of the leading causes of death and it is caused by genetics, nutrition, and unhealthy behaviors. Therefore, changes in lifestyle associated with eating behaviors in diabetes mellitus patients greatly impact on their quality of life. There are many factors related with changes in lifestyle of diabetes mellitus patients, especially eating behaviors. Purpose: This study aims to examine the relationships between self-efficacy, psychological stress, family support, and eating behaviors among type 2 diabetes mellitus (T2DM) patients in Sidoarjo, Indonesia. Method: A total of 117 T2DM patients from the Sidoarjo Community Health Center were included in the analysis. Using SPSS IBM 21.0 program, Pearson product moment correlation was performed to analyze data. Results: The findings showed that self-efficacy and family support had a positive relationship with eating behaviors (r = .692, p < .001; r = .683, p < .001, respectively). Psychological stress had a negative relationship with eating behaviors (r = -.327, p < .001). Conclusion: Self-efficacy, family support, and psychological stress had relationships with eating behaviors. Nurses should pay attention to these factors that make T2DM patients having a long-term commitment in healthy eating behaviors.